Isoprenoid compounds from Euphorbia portlandica. X-ray structure of lupeportlandol, a new lupane triterpene - Madureira,Ana M. (2004)
Phytochemical survey of the Me2CO extracts of the whole dried plant Euphorbia portlandica led to the isolation of a new pentacyclic triterpene alcohol, with the lupane skeleton, named lupeportlandol. Its structure was established as 3alpha-hydroxy-19alphaH-lup-20(29)-ene. The known pentacyclic triterpene glutinol and the steroid b-sitostenone were also isolated. The characterization of the new compound and its acetylated derivative was based on spectroscopic methods and an X-ray diffraction analysis. Lupeportlandol acetate was inactive in cytotoxicity assays in vitro against three human tumor cell lines: MCF-7 (breast cancer), NCI-H460 (non-small cell lung cancer) and SF-268 (CNS cancer).